Comparative RNA sequencing reveals substantial genetic variation in endangered primates - Perry, George H.; Melsted, Páll; Marioni, John C.; Wang, Ying; Bainer, Russell; Pickrell, Joseph K.; Michelini, Katelyn; Zehr, Sarah; Yoder, Anne D.; Stephens, Matthew; Pritchard, Jonathan K.; Gilad, Yoav (Genome Research, 2012)
Comparative genomic studies in primates have yielded important insights into the evolutionary forces that shape genetic diversity and revealed the likely genetic basis for certain species-specific adaptations. To date, however, these studies have focused on only a small number of species. For the majority of nonhuman primates, including some of the most critically endangered, genome-level data are not yet available. In this study, we have taken the first steps toward addressing this gap by sequencing RNA from the livers of multiple individuals from each of 16 mammalian species, including humans and 11 nonhuman primates. Of the nonhuman primate species, five are lemurs and two are lorisoids, for which little or no genomic data were previously available. To analyze these data, we developed a method for de novo assembly and alignment of orthologous gene sequences across species. We assembled an average of 5721 gene sequences per species and characterized diversity and divergence of both gene sequences and gene expression levels. We identified patterns of variation that are consistent with the action of positive or directional selection, including an 18-fold enrichment of peroxisomal genes among genes whose regulation likely evolved under directional selection in the ancestral primate lineage. Importantly, we found no relationship between genetic diversity and endangered status, with the two most endangered species in our study, the black and white ruffed lemur and the Coquerel's sifaka, having the highest genetic diversity among all primates. Our observations imply that many endangered lemur populations still harbor considerable genetic variation. Timely efforts to conserve these species alongside their habitats have, therefore, strong potential to achieve long-term success.